Effect of the preparation of canned "crumbled anchovy" (Engraulis ringens) on polyunsaturated omega 3 fatty acids - Ordoñez, Lenny R. (2014)
The anchoveta (Engraulis ringens) is a major fishery resources exploited in Peru. It is rich source of proteins of high biological value and polyunsaturated fatty acids omega-3: eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The objective was to determine the effect of the process of preparing the canned "crumbled anchovy" with emphasis on polyunsaturated omega-3 fatty acids and true content of them in canning. It was developed following the standardized technology by the Institute of Production Technological (ITP). The chemical, microbiological and physical parameters of total fatty acids profile of canned were evaluated using validated methods by ITP and the Food and Drug Administration (FDA). The amounts of EPA (21,2%) and DHA (15,8%) in raw fillet without skin, decreased with pre-cooking and sterilizing canning to 20,8% and 15,5%, respectively. Histamine levels (2,2 ppm), total volatile bases (9,34 mg%) and the sterility test, indicated that the canning "crumbled anchovy" is a safe product. It is concluded that canning elaboration process not affect significantly the content of polyunsaturated fatty acids omega-3.